Dependence of chromatosome structure on Linker histone sequence and posttranslational modification - Öztürk, Mehmet Ali; Cojocaru, Vlad; Wade, Rebecca C. (Biophysical journal, 2018)
Linker histone (LH) proteins play a key role in higher-order structuring of chromatin for the packing of DNA in eukaryotic cells and in the regulation of genomic function. The common fruit fly (Drosophila melanogaster) has a single somatic isoform of the LH (H1). It is thus a useful model organism for investigating the effects of the LH on nucleosome compaction and the structure of the chromatosome, the complex formed by binding of an LH to a nucleosome. The structural and mechanistic details of how LH proteins bind to nucleosomes are debated. Here, we apply Brownian dynamics simulations to compare the nucleosome binding of the globular domain of D. melanogaster H1 (gH1) and the corresponding chicken (Gallus gallus) LH isoform, gH5, to identify residues in the LH that critically affect the structure of the chromatosome. Moreover, we investigate the effects of posttranslational modifications on the gH1 binding mode. We find that certain single-point mutations and posttranslational modifications of the LH proteins can significantly affect chromatosome structure. These findings indicate that even subtle differences in LH sequence can significantly shift the chromatosome structural ensemble and thus have implications for chromatin structure and transcriptional regulation.